Stereoselective Manganese-Catalyzed Coupling Reaction of Conjugated Chloroenynes and Chlorodienes with Grignard Reagents - Alami, M.; Ramiandrasoa, P.; Cahiez, G. (Synlett, 1998)
In the presence of the soluble complex MnCl2·2LiCl (3%), conjugated chloroenynes and chlorodienes readily react with alkyl Grignard reagents in THF-DMPU to afford stereoselectively enynes and dienes in good to excellent isolated yields.